A Review on Finite Element Analysis Approaches in Durability Assessment of Automotive Components - M. M., Rahman; S., Abdullah; A. K., Ariffin; N. A., Al-Asady (Asian Network for Scientific Information, 2008)

(untitled)
This research describes the majority of interesting findings in the use of the Finite Element Analysis (FEA) based fatigue for automotive components in a form of review write-up. Thus, the theoretical background related to the fatigue life prediction using FEA is presented which is the main subject of this research. The challenge for FEA-based software developers is to deliver reliable fatigue-analysis tools because over designing components is no longer a viable option. Combination between a fatigue model based on the crack initiation, the crack growth and the crack closures are performed with consideration of cycle sequence effect together with finite element results, which lead to the prediction of fatigue life under spectrum or service loadings.